A 2-Year Follow-up Study of an Absorbable Implant to Treat Nasal Valve Collapse - San Nicoló, Marion; Stelter, Klaus; Sadick, Haneen; Bas, Murat; Berghaus, Alexander (Facial Plastic Surgery, 2018)
The safety and effectiveness of an absorbable implant for lateral cartilage support have been recently demonstrated in subjects with nasal valve collapse (NVC) at 12 months postprocedure. This follow-up study aimed to assess whether the safety and effectiveness of the implant persist in these patients for 24 months after the procedure. Thirty subjects with Nasal Obstruction Symptom Evaluation (NOSE) score ≥ 55 and isolated NVC were treated; 14 cases were performed in an operating suite under general anesthesia and 16 cases were performed in a clinic-based setting under local anesthesia. The implant, a polylactic acid copolymer, was placed with a delivery tool within the nasal wall to provide lateral cartilage support. Subjects were followed up through 24 months postprocedure. Fifty-six implants were placed in 30 subjects. The mean preoperative NOSE score was 76.7 ± 14.8, with a range of 55 to 100. At 24 months, the mean score was 32.0 ± 29.3, reflecting an average within-patient reduction of −44.0 ± 31.1 points. There were no device-related adverse events in the 12 to 24 months period. There were five subjects who exited the study prior to the 24-month follow-up. Four of the five subjects who exited were elected for further intervention and one subject was lost to follow-up. This study demonstrates safety of an absorbable implant for lateral nasal wall support and symptom improvement in some subjects with NVC at 24 months postprocedure.
Keywords: nasal airway obstruction; nasal valve collapse; lateral wall insufficiency; implant; rhinoplasty